PENERAPAN SURVEI KARAKTER DAN SURVEI LINGKUNGAN BELAJAR: SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN DI ERA DISRUPSI DIGITAL: - - Nyoman Kiriana; Ni Nyoman Sri Widiasih (Guna Widya: Jurnal Pendidikan Hindu, 2023)
The application of character surveys and learning environment surveys is a form of the National Assessment policy as a substitute for the National Examination. The quality of the education unit is assessed based on student learning outcomes, the teaching and learning process and the climate of the education unit. One of the factors that influence the development of student competence is the character and environmental factors. The demands of the world of work are very high but are not matched by improving the quality of good education, causing new problems in the world of education. The character survey conducted through the Pancasila student profile aims to make students not only have knowledge of Pancasila but are able to practice Pancasila in everyday life. The character survey was conducted to measure students socio-emotional abilities and the most important supporter of the character survey was the teacher. The main characteristics of the Pancasila student profile are fear of God Almighty, and noble character, global diversity, mutual cooperation, independence, critical and creative reasoning. Noble character in students must be fostered through learning at school, the unsuccessful character survey results in students not being able to develop optimally. The learning environment survey explores information related to the quality of learning and the school climate that can support learning which includes a school safety climate, school diversity climate, socio-economic index, learning quality and teacher development.